Removal of Cadmium from Aqueous Solution with Carboxymethyl Cellulose Hydro-gel: Adsorption Conditions and Affecting Factor - Heydarzadeh, H.D.; Gilani, S.L.; Mokhtarian, N.; Kolaei, M.; Soltani, K.A.L. (Asian Journal of Chemistry, 2012)
In this research paper, the possibility of using carboxymethyl cellulose (CMC) synthesized from cotton fibers for the removal of cadmium from aqueous solutions was investigated. The adsorption was found to depend on cadmium initial concentration, pH, CMC dosage, agitation rate and temperature of the experiments. The maximum removal was found to be 96 % for the cadmium concentration of 150 mg L-1 at 40 ºC and pH equal to 11 with 12 gL-1 of CMC by using agitation rate 120 rpm after 3 h. In addition, desorption of cadmium and recovery of it was 95 % at pH = 3. The studies showed that the CMC can be used as an efficient and cost-effective adsorbent material for cadmium removal from wastewater.